Low-expansion low-impedance lithium ion battery negative electrode and preparation method thereof

By introducing the cladding of polypyrrole and single-wall carbon nanotubes on the silicon carbon material of the negative electrode of the lithium-ion battery, and using a gradient structure composite foam copper current collector, the problem of volume expansion and current collector structure stability of the silicon-based material is solved. , realizes a lithium-ion battery negative electrode with low expansion, low impedance and high stability.

CN119447180AActive Publication Date: 2025-02-14广东嘉尚新能源科技有限公司

Patent Information

Application Number
CN202411436399.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The silicon-based material of lithium-ion battery negative electrode material has significant volume expansion problems during charging and discharging, resulting in electrode structure failure and rapid attenuation of electrochemical properties. The existing foam copper current collectors have shortcomings in mechanical strength and structural stability.

Method used

A composite fluid collection, including a composite foam copper layer with gradient density, porosity and thickness distribution, is used, and a coating of polypyrrole and single-wall carbon nanotubes are introduced on the outer surface of the silicon carbon material to form a negative electrode active material coating.

Benefits of technology

Effectively inhibit the expansion of silicon particles, maintain the stability of the electrode structure, reduce the internal resistance of the battery, and improve the circulation and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447180A_ABST
    Figure CN119447180A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery negative electrode with low expansion and low impedance. The lithium ion battery negative electrode comprises a composite current collector and a negative electrode active material coating coated on at least one surface of the composite current collector, the negative electrode active material coating comprises a negative electrode active material, graphene and lithium polyacrylate; the mass ratio of the negative electrode active material to the graphene to the lithium polyacrylate is (90-99): (0.5-5): (0.5-5), the negative electrode active material comprises a silicon carbon material and a coating material layer arranged on the outer surface of the silicon carbon material, and the coating material layer comprises a polypyrrole layer and single-walled carbon nanotubes uniformly distributed in the polypyrrole layer. Compared with the prior art, the lithium ion battery negative electrode provided by the invention has the advantages of low expansion and low impedance, and can effectively inhibit the expansion of silicon particles, reduce the internal resistance of the battery and maintain the structural stability of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a low-swelling and low-impedance lithium ion battery negative electrode and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are widely used in electronic devices and new energy vehicles due to their high energy density and long cycle life. Among the various components of lithium-ion batteries, the negative electrode is crucial to improving the performance and safety of the battery; the negative electrode usually includes a current collector and a negative electrode material layer disposed on the current collector, and its performance directly affects the capacity, rate performance and service life of the battery.

[0003] At present, graphite is the most commonly used negative electrode material for lithium-ion batteries. It is widely used due to its low cost and long cycle life. However, the theoretical specific capacity of graphite is only 372 mAh / g, which is difficult to meet the needs of high energy density batteries. For this reason, researchers began to explore new negative electrode materials, among which silicon-based materials have attracted much attention due to their specific capacity of up to 4200 mAh / g.

[0004] However, silicon-based negative electrodes still face many challenges in practical applications. First, silicon-based materials have a significant volume expansion problem during the charging and discharging process, and the expansion rate can reach more than 300%; this drastic volume change will cause the active material to pulverize and fall off, causing damage to the electrode structure and rapid attenuation of electrochemical performance, which greatly limits the cycle stability of silicon-based materials in practical applications. Secondly, silicon-based materials themselves have poor conductivity, severe polarization during large current charging and discharging, and poor rate performance. In addition, an unstable solid electrolyte interface film (SEI film) is easily formed on the surface of silicon particles in the electrolyte, which continuously consumes electrolyte and lithium ions, resulting in low coulombic efficiency; these problems seriously restrict the commercial application of silicon-based negative electrodes.

[0005] In recent years, the design of composite materials has become an important strategy to improve the performance of silicon-based negative electrode materials. By combining silicon with carbon materials, the volume expansion problem and poor conductivity of silicon can be alleviated to a certain extent, but it is still difficult to meet the increasing performance requirements. Therefore, how to effectively alleviate the volume expansion problem of silicon-based materials, reduce the internal resistance of the battery, and improve its cycle performance is a major challenge in the current research on negative electrode materials for lithium batteries.

[0006] In addition, the negative electrode current collector acts as a carrier of active materials and an electron transport channel, and its performance has an important impact on the energy density, rate performance and cycle stability of the battery. At present, copper foil is commonly used as the current collector material for the negative electrode of commercial lithium-ion batteries. However, copper foil current collectors have problems such as low specific surface area and limited active material loading, making it difficult to further improve the energy density of the battery. In order to solve this problem, the researchers proposed a design scheme using copper foam as the negative electrode current collector.

[0007] However, the existing copper foam current collector generally adopts a single-layer uniform porosity and density design. While improving the specific surface area and conductivity, it often sacrifices the mechanical strength and structural stability of the current collector. It is easy to deform or break during battery assembly and charging and discharging, resulting in problems such as active material shedding and increased interface impedance, which seriously affects the performance and cycle life of the battery. In addition, the stress distribution of the single-layer copper foam current collector is uneven, and it is easy to be damaged in the stress concentration area, further reducing the mechanical stability and reliability of the current collector. Therefore, designing and preparing a current collector with high specific surface area, high conductivity, high mechanical strength and high structural stability is also crucial to improving the performance of the battery negative electrode.

[0008] In summary, developing a low-expansion and low-impedance lithium-ion battery negative electrode that can effectively inhibit the expansion of silicon particles and maintain the stability of the electrode structure has become an important topic in current lithium-ion battery negative electrode research. Summary of the invention

[0009] The main purpose of the present invention is to provide a low-expansion and low-impedance lithium-ion battery negative electrode to address the deficiencies of the prior art, which can effectively inhibit the expansion of silicon particles and maintain the stability of the electrode structure.

[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0011] A low-expansion, low-impedance negative electrode for a lithium-ion battery comprises a composite current collector and a negative electrode active material coating coated on at least one surface of the composite current collector; the negative electrode active material coating comprises a negative electrode active material, graphene and lithium polyacrylate; the mass ratio of the negative electrode active material, the graphene and the lithium polyacrylate is (90-99):(0.5-5):(0.5-5), the negative electrode active material comprises a silicon-carbon material and a coating material layer arranged on the outer surface of the silicon-carbon material, the coating material layer comprises a polypyrrole layer and single-walled carbon nanotubes uniformly distributed in the polypyrrole layer.

[0012] Preferably, the silicon-carbon material is a mixture of silicon-based particles and graphite particles in a mass ratio of 1:(0.5-1); the particle size of the silicon-based particles is 10-50 nm.

[0013] Preferably, the particle size of the negative electrode active material particles is 0.2-2 μm.

[0014] Preferably, a multifunctional regulating coating is further provided between the composite current collector and the negative electrode active material coating, the multifunctional regulating coating comprising barium titanate, conductive carbon black and lithium polyacrylate, and the mass ratio of the barium titanate, conductive carbon black and lithium polyacrylate is 1:1:(0.5~1).

[0015] Preferably, the thickness of the multifunctional regulating coating is 0.1~1 μm.

[0016] Preferably, the preparation method of the negative electrode active material is as follows:

[0017] (1) mixing graphite particles and distilled water in a mass ratio of 1:(10-20), stirring for 1-3 hours, and uniformly mixing to form a first mixture; then adding silicon-based particles to the first mixture, stirring for 1-3 hours, and uniformly mixing the graphite particles and the silicon-based particles to form a second mixture;

[0018] (2) mixing pyrrole monomer and single-walled carbon nanotube in a mass ratio of 1:(0.05-0.1), dissolving in a hydrogen chloride solution and stirring evenly to form a third mixture, wherein the mass ratio of pyrrole monomer to hydrogen chloride solution is 1:(1-5), then adding the second mixture to the third mixture, stirring for 0.5-2h, so that the second mixture and the third mixture are evenly mixed to form a fourth mixture;

[0019] (3) dissolving ammonium persulfate in a hydrogen chloride solution to form a fifth mixture, wherein the mass ratio of ammonium persulfate to hydrogen chloride solution is 1:(1-5), adding the fourth mixture to the fifth mixture, stirring and reacting for 2-4 hours, filtering, washing and drying in sequence, and obtaining the negative electrode active material.

[0020] Among them, pyrrole monomer can be quickly polymerized into chains to form polypyrrole when added with ammonium persulfate; adding hydrogen chloride can provide an acidic environment, enhance the oxidizing property of ammonium persulfate, and increase the degree of polymerization of pyrrole.

[0021] Preferably, the composite current collector includes a copper foil layer and a composite copper foam layer arranged on the copper foil layer, the composite copper foam layer includes a first copper foam, a second copper foam and a third copper foam arranged in sequence from the inside to the outside, the density ρ1 of the first copper foam, the density ρ2 of the second copper foam and the density ρ3 of the third copper foam satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first copper foam, the porosity φ2 of the second copper foam and the porosity φ3 of the third copper foam satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first copper foam, the thickness h2 of the second copper foam and the thickness h3 of the third copper foam satisfy the relationship: h1<h2<h3.

[0022] Among them, the negative electrode of the present invention adopts a composite current collector of copper foil and composite foam copper. First, the composite foam copper layer has a high specific surface area and a three-dimensional network structure, which is not only conducive to the infiltration of the electrolyte, but also can load more active materials and is conducive to the uniform distribution of active materials, which can shorten the transmission path of electrons and ions, reduce the interface resistance, and improve the energy density and rate performance of the battery. Secondly, the composite foam copper with gradient density, porosity and thickness distribution of the present invention can realize the layer-by-layer transmission and buffering of stress, avoid stress concentration leading to local deformation, fracture or destruction of the current collector, and improve the mechanical stability and reliability of the current collector. Thirdly, the composite foam copper with gradient density, porosity and thickness distribution of the present invention can not only significantly improve the specific surface area and conductivity of the current collector, but also take into account mechanical strength and structural stability, effectively solving the problem that the existing single-layer foam copper current collector is prone to deformation and fracture. In addition, the second and third layers of low-density and high-porosity copper foam can provide a larger specific surface area, which is beneficial to the loading of active materials and the infiltration of electrolytes, thereby improving the energy density and rate performance of the battery; while the first layer of copper foam has a relatively high density and low porosity, which can provide sufficient mechanical support and anti-deformation ability to ensure the structural integrity and stability of the composite current collector.

[0023] Preferably, the density ρ1 of the first copper foam is 0.5-0.9 g / cm³, the density ρ2 of the second copper foam is 0.3-0.5 g / cm³, and the density ρ3 of the third copper foam is 0.1-0.3 g / cm³; the porosity φ1 of the first copper foam is 50-70%, the porosity φ2 of the second copper foam is 70-85%, and the porosity φ3 of the third copper foam is 85-95%; the thickness h1 of the first copper foam is 0.5-1 μm, the thickness h2 of the second copper foam is 1-2 μm, and the thickness h3 of the third copper foam is 2-4 μm; the thickness h4 of the copper foil layer is 0.5-1 μm; and the total thickness of the composite current collector is 4-8 μm.

[0024] Preferably, the pore size d1 of the first copper foam, the pore size d2 of the second copper foam and the pore size d3 of the third copper foam satisfy the relationship: d1<d2<d3; the pore size d1 of the first copper foam is 1~5μm, the pore size d2 of the second copper foam is 5~10μm, and the pore size d3 of the third copper foam is 10~15μm.

[0025] Preferably, the surface of the composite copper foam layer is further provided with a carbon nano-coating, and the thickness of the carbon nano-coating is 10-20 nm.

[0026] In addition, the present invention also provides a method for preparing the above-mentioned low expansion and low impedance lithium ion battery negative electrode, comprising the following steps:

[0027] 1) preparing a first copper foam layer slurry, a second copper foam layer slurry and a third copper foam layer slurry respectively;

[0028] a. The first copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(15~25):1, anhydrous ethanol is added, and the solid content is adjusted to 30-50wt%; wherein the particle size of the copper powder is 0.1~0.4μm, and the particle size of the urea is 0.2~0.5μm;

[0029] b. The second copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (25-35): 1, anhydrous ethanol is added, and the solid content is adjusted to 15-30wt%; wherein the particle size of the copper powder is 0.2-0.8μm, and the particle size of the urea is 0.4-1μm;

[0030] c. The third copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, anhydrous ethanol is added, and the solid content is adjusted to 5-15wt%; wherein the particle size of the copper powder is 0.5-1.5μm, and the particle size of the urea is 0.8-1.8μm;

[0031] 2) preheating the copper foil substrate, and then coating the first copper foam layer slurry, the second copper foam layer slurry and the third copper foam layer slurry on the copper foil substrate in sequence, and spraying a small amount of anhydrous ethanol on the surface of each layer of slurry during the coating process;

[0032] 3) Place the coated copper foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the copper powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient foam copper layer;

[0033] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried;

[0034] 5) Mixing the negative electrode active material, graphene and lithium polyacrylate in a mass ratio of (90-99):(0.5-5):(0.5-5) in deionized water and stirring evenly to obtain a negative electrode active material coating slurry;

[0035] 6) coating the negative electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain the negative electrode of the lithium ion battery.

[0036] Preferably, step 4) further comprises surface modification of the composite current collector obtained after cooling, depositing a 10-20 nm thick carbon nanocoating, and hot rolling the surface modified composite current collector on a precision rolling mill at a rolling temperature of 100-150° C. and a rolling rate of 5-10%.

[0037] Compared with the prior art, the present invention has at least the following beneficial effects:

[0038] 1) The present invention forms a negative electrode active material by introducing a coating layer of polypyrrole and single-walled carbon nanotubes on the outer surface of the silicon-carbon material, which can effectively prevent the structural damage of silicon particles caused by volume change during the charge and discharge process; wherein, polypyrrole has high electrical conductivity, good environmental stability and strong charge storage capacity, so the polypyrrole layer as a flexible coating layer can buffer the volume change of silicon particles during the charge and discharge process, reduce stress accumulation, and improve the conductivity and structural stability of the electrode, while the single-walled carbon nanotubes can continuously and effectively contact the silicon material during the cycle process due to their high aspect ratio and flexibility, preventing the conductive network from breaking, and the synergistic effect of the two can effectively inhibit the expansion and pulverization of silicon particles, maintain the integrity of the electrode structure, and improve the cycle life and stability of the lithium battery.

[0039] 2) The single-walled carbon nanotubes added in the present invention have excellent electronic conductivity, and together with graphene form a line-surface conductive network, which significantly improves the conductivity of the electrode and reduces the battery interface impedance. Moreover, the formed three-dimensional conductive network not only establishes a good conductive channel between the silicon-carbon negative electrode particles, but also can wrap, entangle or bind the negative electrode active material, further inhibiting the expansion of the negative electrode; in addition, the high adhesion of the single-walled carbon nanotubes (2 times higher than that of multi-walled carbon nanotubes) further enhances the stability of the electrode structure.

[0040] 3) The negative electrode active material coating of the present invention further optimizes the conductive network and structural stability of the material by further adding graphene and lithium polyacrylate to the negative electrode active material. After the introduction of the graphene conductive agent, it can work synergistically with the single-walled carbon nanotubes to form a line-surface three-dimensional conductive network between the active material particles, provide an efficient electron transmission channel, reduce the contact resistance between particles, and improve the conductive performance of the electrode. At the same time, lithium polyacrylate, as a binder, can firmly bond the active material particles together, prevent the particles from pulverizing and falling off due to volume changes during the charge and discharge process, and improve the structural stability and mechanical strength of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a schematic structural diagram of a negative electrode active material in one embodiment of the present invention;

[0042] Figure 2 is a schematic structural diagram of a negative electrode in one embodiment of the present invention;

[0043] Figure 3 is a schematic structural diagram of a negative electrode in another embodiment of the present invention;

[0044] Figure 4 Schematic diagram of the structure of a composite current collector of a negative electrode in one embodiment of the present invention;

[0045] Figure 5 Schematic diagram of the structure of a composite current collector of a negative electrode in another embodiment of the present invention.

[0046] In the figure: 1. composite current collector; 11. copper foil layer; 12. composite foam copper layer; 121. first foam copper; 122. second foam copper; 123. third foam copper; 13. carbon nanocoating; 2. negative electrode active material coating; 3. multifunctional regulating coating; 100. negative electrode active material; 101. graphite particles; 102. silicon-based particles; 103. polypyrrole layer; 104. single-walled carbon nanotube. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Please refer to the attached Figure 1~2 and Figure 4 The present application provides a low-expansion and low-impedance lithium-ion battery negative electrode, comprising a composite current collector 1 and a negative electrode active material coating 2 coated on at least one surface of the composite current collector 1; the negative electrode active material coating 2 comprises a negative electrode active material 100, graphene and lithium polyacrylate; the mass ratio of the negative electrode active material 100, graphene and lithium polyacrylate is (90~99):(0.5~5):(0.5~5), the negative electrode active material 100 comprises a silicon-carbon material and a coating material layer arranged on the outer surface of the silicon-carbon material, the coating material layer comprises a polypyrrole layer 103 and single-walled carbon nanotubes 104 uniformly distributed in the polypyrrole layer 103.

[0049] Among them, the present invention adopts a silicon-carbon composite negative electrode material coated with polypyrrole and single-walled carbon nanotubes 104, which can effectively inhibit the expansion, powdering and shedding of silicon-based particles 102. At the same time, the single-walled carbon nanotubes 104 have a higher length-diameter ratio, and thus have higher flexibility. During the cycle process, the single-walled carbon nanotubes 104 can effectively contact the silicon material to avoid detachment and failure, thereby improving the cycle performance of the lithium battery.

[0050] Among them, polypyrrole has high electrical conductivity, good environmental stability, reversible electrochemical redox characteristics and strong charge storage capacity, and is an ideal electrode material, and also acts as a coating agent; among them, the one-dimensional single-walled carbon nanotube 104 is cylindrical, hollow inside, and has good electronic conductivity. Its fiber structure can contact the electrode active material point to line, forming a continuous conductive network in the electrode active material, acting as a "wire", which is beneficial to improve battery capacity, rate performance, battery cycle life, and reduce battery interface impedance. Among them, compared with multi-walled carbon nanotubes, single-walled carbon nanotubes 104 have the following performance advantages: 1) Stronger conductivity: Because single-walled carbon nanotubes 104 have a higher aspect ratio, the conductivity is better, and the addition amount is less. A lower addition amount can form a high-quality conductive network, and play the same or even better conductive effect; 2) Better safety: Single-walled carbon nanotubes 104 have up to 2 times the adhesion of multi-walled carbon nanotubes or conductive carbon black, and better safety. 3) Improve the cycle life of silicon-based negative electrode batteries: Silicon-based negative electrodes have weak conductivity, and single-walled carbon tubes can perfectly make up for their shortcomings and significantly improve the cycle life.

[0051] Among them, the silicon-carbon negative electrode material system of the present invention uses single-walled carbon nanotubes 104 and graphene in combination, so that a line-surface conductive network is formed between the silicon-carbon negative electrode particles, and a good conductive channel is established between the silicon-carbon negative electrode particles. At the same time, this line-surface three-dimensional conductive network can wrap, entangle or bind the negative electrode active material 100, thereby inhibiting the expansion of the negative electrode, greatly reducing the expansion rate of the electrode sheet, and improving the stability of the battery cycle.

[0052] In addition, the negative electrode active material coating 2 of the present invention further optimizes the conductive network and structural stability of the material by further adding graphene and lithium polyacrylate to the negative electrode active material 100. After the graphene conductive agent is introduced, it can work synergistically with the single-walled carbon nanotubes 104 to form a line-surface three-dimensional conductive network between the active material particles, provide an efficient electron transmission channel, reduce the contact resistance between particles, and improve the conductive performance of the electrode. At the same time, lithium polyacrylate, as a binder, can firmly bond the active material particles together, prevent the particles from pulverizing and falling off due to volume changes during the charge and discharge process, and improve the structural stability and mechanical strength of the electrode.

[0053] In summary, the present invention realizes a negative electrode of a lithium-ion battery with low expansion, low impedance and high stability through multiple structural designs and material selections.

[0054] In one embodiment of the present application, the silicon-carbon material is a mixture of silicon-based particles 102 and graphite particles 101 in a mass ratio of 1: (0.5~1); the particle size of the silicon-based particles 102 is 10~50nm. Among them, the silicon-based particles 102 are preferably silicon oxide. By combining nano-silicon particles with graphite particles 101, the volume expansion of silicon particles can be buffered while ensuring high specific capacity. In addition, by optimizing the ratio of silicon-based particles 102 to graphite particles 101 and the particle size of silicon-based particles 102, the negative impact of silicon expansion can be minimized while ensuring high capacity. The particle size of silicon-based particles 102 of 10~50nm helps to alleviate volume expansion, and the mixture formed with graphite can improve the overall conductivity and stability.

[0055] In one embodiment of the present application, the particle size of the negative electrode active material 100 is 0.2-2 μm. The present invention controls the particle size of the negative electrode active material 100 to 0.2-2 μm, which can significantly increase the specific surface area of ​​the material, shorten the ion diffusion path, and thus improve the rate performance of the material.

[0056] In one embodiment according to the present application, Figure 3 As shown, a multifunctional regulating coating 3 is also provided between the composite current collector 1 and the negative electrode active material coating 2. The multifunctional regulating coating 3 includes barium titanate, conductive carbon black and lithium polyacrylate. The mass ratio of barium titanate, conductive carbon black and lithium polyacrylate is 1:1:(0.5~1).

[0057] Among them, the introduced barium titanate, as a ferroelectric material, can induce its internal dipoles to be oriented under the action of an external electric field, so that a uniform negative charge layer is formed on the surface of the composite current collector 1. This negative charge layer can promote the uniform deposition of Li+ on the surface of the negative electrode, inhibit the growth of lithium dendrites, thereby alleviating local stress concentration, reducing the degree of fragmentation of silicon particles, and extending the battery cycle life. On the other hand, barium titanate also has piezoelectric properties. During the cycle, the volume expansion of the composite material will cause the barium titanate lattice to deform, causing dynamic changes in the local built-in electric field. This dynamic electric field can guide lithium ions to migrate to areas with less stress, achieve uniform distribution of lithium ions, and avoid electrode pulverization failure caused by stress concentration. In addition, conductive carbon black can improve the conductivity of the coating, and lithium polyacrylate plays a bonding role. Therefore, the setting of the multifunctional control coating 3 can further inhibit the expansion of the silicon-based negative electrode, improve the distribution of lithium ions, inhibit the growth of lithium dendrites, and improve battery performance.

[0058] In one embodiment of the present application, the thickness of the multifunctional control coating 3 is 0.1-1 μm. This thickness range can ensure the effective performance of the coating function without significantly increasing the total thickness and weight of the negative electrode and reducing the battery energy density.

[0059] In one embodiment of the present application, the preparation method of the negative electrode active material 100 is as follows:

[0060] (1) mixing graphite particles 101 and distilled water at a mass ratio of 1:(10-20), stirring for 1-3 hours, and uniformly mixing to form a first mixture; then adding silicon-based particles 102 to the first mixture, stirring for 1-3 hours, and uniformly mixing the graphite particles 101 and the silicon-based particles 102 to form a second mixture;

[0061] (2) mixing pyrrole monomer and single-walled carbon nanotube 104 in a mass ratio of 1:(0.05-0.1), dissolving in a hydrogen chloride solution and stirring evenly to form a third mixture, wherein the mass ratio of pyrrole monomer to hydrogen chloride solution is 1:(1-5), then adding the second mixture to the third mixture and stirring for 0.5-2h to uniformly mix the second mixture and the third mixture to form a fourth mixture;

[0062] (3) dissolving ammonium persulfate in a hydrogen chloride solution to form a fifth mixture, wherein the mass ratio of ammonium persulfate to hydrogen chloride solution is 1:(1-5), adding the fourth mixture to the fifth mixture, stirring and reacting for 2-4 hours, filtering, washing and drying in sequence, and obtaining the negative electrode active material 100.

[0063] Among them, pyrrole monomer can be quickly polymerized into chains to form polypyrrole by adding ammonium persulfate; adding hydrogen chloride can provide an acidic environment, enhance the oxidizing property of ammonium persulfate, and increase the polymerization degree of pyrrole.

[0064] The preparation of the negative electrode active material 100 of the present invention firstly premixes the silicon-based particles 102 and the graphite particles 101, and then mixes them with the pyrrole monomer and the single-walled carbon nanotube 104; then, in-situ polymerization is carried out under the condition that ammonium persulfate is used as an initiator and hydrogen chloride provides an acidic environment. Among them, by premixing the silicon-based particles 102 and the graphite particles 101, the two materials can be uniformly dispersed at the nanoscale to prevent silicon particles from agglomerating. Subsequently, the pyrrole monomer and the single-walled carbon nanotube 104 are introduced, and in the process of in-situ polymerization, the polypyrrole and the carbon nanotube can be synchronously and uniformly coated on the silicon-carbon particles to obtain a composite material with uniform structure and good dispersibility. The ammonium persulfate initiator and the acidic environment of hydrogen chloride can accelerate the polymerization rate of pyrrole and improve the degree of polymerization and conductivity of polypyrrole.

[0065] In one embodiment of the present application, the composite current collector 1 includes a copper foil layer 11 and a composite copper foam layer 12 arranged on the copper foil layer 11, the composite copper foam layer 12 includes a first copper foam 121, a second copper foam 122 and a third copper foam 123 arranged in sequence from the inside to the outside, and the density ρ1 of the first copper foam 121, the density ρ2 of the second copper foam 122 and the density ρ3 of the third copper foam 123 satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first copper foam 121, the porosity φ2 of the second copper foam 122 and the porosity φ3 of the third copper foam 123 satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first copper foam 121, the thickness h2 of the second copper foam 122 and the thickness h3 of the third copper foam 123 satisfy the relationship: h1<h2<h3.

[0066] The composite copper foam current collector of the present invention adopts a hierarchical structure design, which can significantly improve the mechanical strength and structural stability of the current collector while ensuring high specific surface area and conductivity. The presence of the inner layer of high-density copper foam can effectively bear the mechanical load of the current collector and prevent deformation and breakage; while the outer layer of low-density copper foam can provide a larger specific surface area and porosity, promoting electrolyte infiltration and ion transmission. Therefore, the hierarchical structure design effectively balances the multiple performance requirements of the current collector and significantly improves the comprehensive performance of the battery negative electrode.

[0067] Among them, although the traditional single-layer copper foam current collector has a high specific surface area and porosity, its mechanical strength and structural stability are poor; it is difficult to withstand the stress impact during battery assembly and charging and discharging; it is easy to deform or break, resulting in problems such as active material shedding and increased interface impedance. After the hierarchical structure design is adopted in the present invention, the inner layer of high-density copper foam can be used as a mechanical support layer to provide sufficient mechanical strength and rigidity to prevent the current collector from deforming and breaking; the middle layer has a moderate density and plays a transition and connection role; the outer layer of low-density copper foam can maximize the specific surface area and porosity, promote electrolyte infiltration and ion transfer, and reduce interface impedance. At the same time, this hierarchical structure can also achieve a gradient distribution of stress to avoid local damage caused by stress concentration. Therefore, the hierarchical structure copper foam current collector can ensure high specific surface area and conductivity while taking into account mechanical strength and structural stability, thereby improving the applicability and reliability of the current collector in the negative electrode of the battery.

[0068] In summary, the composite current collector 1 of the present invention comprises a copper foil layer 11 and a composite copper foam layer 12, wherein the composite copper foam layer 12 is composed of three layers of copper foams with different densities, different porosities and different thicknesses, which are distributed in a gradient manner. This structure has the following outstanding advantages:

[0069] 1) High specific surface area: The gradient-distributed composite copper foam layer 12 has a high specific surface area and a three-dimensional porous structure as a whole. The outer layer of low-density, high-porosity and thicker copper foam can load more active substances, improve the utilization rate of active materials, and increase battery capacity.

[0070] 2) High conductivity: The outer layer of copper foam is in direct contact with the active material, and its loose and porous structure is conducive to the infiltration of electrolyte and the rapid transmission of ions, thereby reducing the interface resistance. The inner layer of copper foam with high density and low porosity can provide an effective electron transmission channel, ensuring the high conductivity of the current collector.

[0071] 3) High mechanical strength: The inner layer of high-density, low-porosity and thin copper foam can provide sufficient mechanical support to ensure the structural integrity of the current collector; the middle layer has moderate density and porosity, which plays a transition and buffering role and improves the mechanical stability of the current collector.

[0072] 4) High structural stability: The gradient structure design can achieve layer-by-layer transmission and uniform distribution of stress. The outer layer of low-density, high-porosity and thick copper foam can effectively absorb and buffer the stress generated during the battery charging and discharging process, avoid stress concentration leading to local deformation or fracture of the current collector, and extend the cycle life of the battery.

[0073] In one embodiment of the present application, the density ρ1 of the first copper foam 121 is 0.5-0.9 g / cm³, preferably 0.7 g / cm³, the density ρ2 of the second copper foam 122 is 0.3-0.5 g / cm³, preferably 0.4 g / cm³, and the density ρ3 of the third copper foam 123 is 0.1-0.3 g / cm³, preferably 0.2 g / cm³; the porosity φ1 of the first copper foam 121 is 50-70%, preferably 60 %, the porosity φ2 of the second copper foam 122 is 70-85%, preferably 80%, the porosity φ3 of the third copper foam 123 is 85-95%, preferably 90%; the thickness h1 of the first copper foam 121 is 0.5-1μm, the thickness h2 of the second copper foam 122 is 1-2μm, and the thickness h3 of the third copper foam 123 is 2-4μm; the thickness h4 of the copper foil layer 11 is 0.5-1μm; the total thickness of the composite current collector 1 is 4-8μm.

[0074] By rationally designing the above parameters, the specific surface area and conductivity of the current collector can be maximized while ensuring the mechanical strength and structural stability. For example, by appropriately reducing the density of the inner layer of copper foam and increasing the porosity, the specific surface area can be increased while ensuring the mechanical strength, promoting electrolyte infiltration and ion transport; and by appropriately reducing the thickness and pore size of the outer layer of copper foam, a higher specific surface area and a smaller pore size can be obtained, the loading amount of active materials can be increased and the ion diffusion path can be shortened. At the same time, optimizing the thickness ratio of each layer of copper foam can achieve the best balance between mechanical strength and specific surface area. Therefore, by rationally designing the structural parameters of the composite copper foam current collector, the conductivity and specific surface area of ​​the current collector can be maximized while ensuring mechanical stability, thereby improving the rate performance and cycle performance of the battery negative electrode. In addition, the total thickness of the negative electrode composite current collector 1 of the present invention is controlled within the ultra-thin range of 4-8μm, which can significantly reduce the thickness and mass of the current collector compared with the traditional copper foil current collector, further improve the energy density and specific power of the battery, and is conducive to the miniaturization and lightweight design of the battery. In addition, the thickness of each copper foam layer will also directly affect the performance of the battery; if the thickness of each copper foam layer is insufficient, the active material particles may be squeezed out of the pores or destroyed under pressure, which will reduce the overall performance of the electrode, resulting in a decrease in the rate performance and cycle life of the battery; on the other hand, if the thickness of each copper foam layer is too large, the proportion of inactive materials will increase, thereby reducing the energy density of the battery. Therefore, controlling the appropriate thickness of each copper foam layer is crucial to optimizing the performance of lithium-ion batteries.

[0075] In one embodiment of the present application, the pore size d1 of the first copper foam 121, the pore size d2 of the second copper foam 122, and the pore size d3 of the third copper foam 123 satisfy the relationship: d1<d2<d3; the pore size d1 of the first copper foam 121 is 1~5μm, preferably 3μm, the pore size d2 of the second copper foam 122 is 5~10μm, preferably 8μm, and the pore size d3 of the third copper foam 123 is 10~15μm, preferably 13μm. The horn-shaped distribution of the pore size gradient can form a multi-level porous structure that is conducive to the diffusion of lithium ions and the embedding of active substances. The large pore size of the outer layer is conducive to the rapid transmission of electrolyte and lithium ions, and the small pore size of the inner layer can inhibit the volume expansion of the active substance, maintain the stability of the electrode structure, and improve the rate performance and cycle stability of the battery. In addition, the size of the pores has a decisive influence on the permeability of the slurry. If the pore size is too small, the slurry may not be able to effectively fill the pores due to the surface tension of the slurry, which will hinder the uniform distribution of the active material and affect the performance of the electrode. On the contrary, if the pore size is too large, the slurry will easily overfill the pores, resulting in an increase in the surface density. During the drying process, this overfilling may cause local cracks, further affecting the rate performance of the battery. Therefore, choosing the right pore size is crucial to ensuring the quality of the electrode and battery performance.

[0076] In one embodiment according to the present application, Figure 5 As shown, the surface of the composite copper foam layer 12 is also provided with a carbon nano coating 13, and the thickness of the carbon nano coating 13 is 10-20nm. Coating the carbon nano coating 13 on the surface of the composite copper foam can further improve the conductivity and corrosion resistance of the current collector. The carbon nano coating 13 is tightly combined with the copper foam matrix to form a dense and uniform conductive protective layer on the surface of the current collector, which effectively reduces the interface resistance, while also improving the chemical stability of the current collector in the electrolyte environment and extending the cycle life of the battery. In addition, the appropriate thickness of the carbon nano coating 13 can avoid the pore blockage or increase of the interface impedance caused by the coating being too thick.

[0077] Among them, although the copper foam has excellent electrical conductivity and specific surface area, its surface may be corroded by the electrolyte, generating an insulating copper oxide passivation layer, resulting in increased interface impedance and battery performance attenuation. By coating a layer of carbon nano coating 13 on the surface of the copper foam, the direct contact between the copper foam and the electrolyte can be effectively isolated to prevent the occurrence of corrosion reactions. At the same time, the carbon nano coating 13 itself has excellent electrical conductivity, and can form a uniform and dense conductive network on the surface of the copper foam, reduce the interface resistance, and improve the conductivity of the current collector. In addition, the carbon nano coating 13 also has excellent chemical stability, can be stably present in the electrolyte environment for a long time, delay the attenuation of the current collector performance, and improve the cycle life of the battery. Therefore, the introduction of the carbon nano coating 13 can further optimize the performance of the composite copper foam current collector from the two aspects of conductivity and corrosion resistance, and provide a better current collector material for the negative electrode of high-performance lithium-ion batteries.

[0078] In addition, the present application also provides a method for preparing the above-mentioned low expansion and low impedance lithium ion battery negative electrode, comprising the following steps:

[0079] 1) preparing a first copper foam layer slurry, a second copper foam layer slurry and a third copper foam layer slurry respectively;

[0080] a. The first copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(15-25):1, anhydrous ethanol is added, and the solid content is adjusted to 30-50wt%; wherein the particle size of the copper powder is 0.1-0.4μm, and the particle size of the urea is 0.2-0.5μm;

[0081] b. The second copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (25-35): 1, anhydrous ethanol is added, and the solid content is adjusted to 15-30wt%; wherein the particle size of the copper powder is 0.2-0.8μm, and the particle size of the urea is 0.4-1μm;

[0082] c. The third copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, anhydrous ethanol is added, and the solid content is adjusted to 5-15wt%; wherein the particle size of the copper powder is 0.5-1.5μm, and the particle size of the urea is 0.8-1.8μm;

[0083] 2) preheating the copper foil substrate, and then coating the first copper foam layer slurry, the second copper foam layer slurry and the third copper foam layer slurry on the copper foil substrate in sequence, and spraying a small amount of anhydrous ethanol on the surface of each layer of slurry during the coating process;

[0084] 3) Place the coated copper foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the copper powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient foam copper layer;

[0085] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried;

[0086] 5) Mixing the negative electrode active material, graphene and lithium polyacrylate in a mass ratio of (90-99):(0.5-5):(0.5-5) in deionized water and stirring evenly to obtain a negative electrode active material coating slurry;

[0087] 6) coating the negative electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain the negative electrode of the lithium ion battery.

[0088] Among them, the negative electrode current collector preparation method of the present invention adopts a process route of gradient slurry ratio and layer-by-layer coating and sintering, which is simple to operate and easy to control. By adjusting the slurry components, solid content, particle size and coating process parameters, the microstructural parameters such as density, porosity, thickness and pore size of the composite copper foam can be accurately controlled to ensure the consistency and repeatability of the current collector performance. In addition, by controlling the particle size of copper powder and urea pore former in different layers of slurry, the pore size and porosity of the copper foam can be effectively controlled to ensure the formation of a gradient structure, while avoiding problems such as incomplete sintering or pore collapse caused by excessive or small particle size. Therefore, the negative electrode preparation process proposed by the present invention is simple and controllable to operate, and is easy to promote and apply in industrialization.

[0089] In one embodiment of the present application, step 4) further includes surface modification of the composite current collector 1 obtained after cooling, depositing a 10-20 nm thick carbon nano coating 13, and hot rolling the surface modified composite current collector 1 on a precision rolling mill, with a rolling temperature of 100-150°C and a rolling rate of 5-10%. The introduction of surface modification and hot rolling processes can further improve the conductivity and bonding strength of the composite current collector 1, and improve the interface compatibility and mechanical properties between the current collector and the active material coating.

[0090] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.

[0091] Example 1

[0092] Preparation of negative electrode sheet:

[0093] The negative electrode of the lithium-ion battery of this embodiment includes a composite current collector 1 and a negative electrode active material coating 2 coated on a surface of the composite current collector 1; the negative electrode active material coating 2 includes a negative electrode active material 100, graphene and lithium polyacrylate; the mass ratio of the negative electrode active material 100, graphene and lithium polyacrylate is 96:2:2, the negative electrode active material 100 includes a silicon-carbon material and a coating material layer arranged on the outer surface of the silicon-carbon material, the coating material layer includes a polypyrrole layer 103 and single-walled carbon nanotubes 104 uniformly distributed in the polypyrrole layer 103.

[0094] The silicon-carbon material is a mixture of silicon oxide particles and graphite particles 101 in a mass ratio of 1:1; the particle size of the silicon oxide particles is 25 nm; and the particle size of the negative electrode active material 100 particles is 0.5 μm.

[0095] The preparation method of the negative electrode active material is as follows:

[0096] (1) mixing graphite particles and distilled water at a mass ratio of 1:15, stirring for 2 hours, and mixing evenly to form a first mixture; then adding silicon dioxide particles to the first mixture, stirring for 2 hours, and mixing the graphite particles and silicon dioxide particles evenly to form a second mixture;

[0097] (2) mixing pyrrole monomer and single-walled carbon nanotube in a mass ratio of 1:0.05, dissolving in a hydrogen chloride solution and stirring to form a third mixture, wherein the mass ratio of pyrrole monomer to hydrogen chloride solution is 1:3, and then adding the second mixture to the third mixture and stirring for 1 hour to mix the second mixture and the third mixture to form a fourth mixture;

[0098] (3) dissolving ammonium persulfate in a hydrogen chloride solution to form a fifth mixture, wherein the mass ratio of ammonium persulfate to hydrogen chloride solution is 1:3, adding the fourth mixture to the fifth mixture, stirring and reacting for 3 hours, filtering, washing and drying in sequence, thereby obtaining the negative electrode active material.

[0099] The composite current collector 1 includes a copper foil layer 11 and a composite copper foam layer 12 disposed on the copper foil layer 11, wherein the composite copper foam layer 12 is composed of three layers of copper foams with different densities, different porosities and different thicknesses; the composite current collector 1 is connected to a negative electrode tab;

[0100] The composite copper foam layer 12 includes a first copper foam 121, a second copper foam 122 and a third copper foam 123 which are arranged in sequence from the inside to the outside. The density ρ1 of the first copper foam 121, the density ρ2 of the second copper foam 122 and the density ρ3 of the third copper foam 123 satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first copper foam 121, the porosity φ2 of the second copper foam 122 and the porosity φ3 of the third copper foam 123 satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first copper foam 121, the thickness h2 of the second copper foam 122 and the thickness h3 of the third copper foam 123 satisfy the relationship: h1<h2<h3.

[0101] Specifically, in this embodiment, the density ρ1 of the first copper foam 121 is 0.7g / cm³, the density ρ2 of the second copper foam 122 is 0.4g / cm³, and the density ρ3 of the third copper foam 123 is 0.2g / cm³. The porosity φ1 of the first copper foam 121 is 60%, the porosity φ2 of the second copper foam 122 is 80%, and the porosity φ3 of the third copper foam 123 is 90%. The thickness h1 of the first copper foam 121 is 0.5μm, the thickness h2 of the second copper foam 122 is 1.5μm, and the thickness h3 of the third copper foam 123 is 3μm; the thickness h4 of the copper foil layer 11 is 1μm; the total thickness of the composite current collector 1 is 6μm.

[0102] The preparation method of the negative electrode sheet is as follows:

[0103] 1) preparing a first copper foam layer slurry, a second copper foam layer slurry and a third copper foam layer slurry respectively;

[0104] a. The first copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:20:1, anhydrous ethanol is added, and the solid content is adjusted to 40wt%; wherein the particle size of the copper powder is 0.2μm, and the particle size of the urea is 0.4μm;

[0105] b. The second copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:30:1, anhydrous ethanol is added, and the solid content is adjusted to 25wt%; wherein the particle size of the copper powder is 0.5μm, and the particle size of the urea is 0.8μm;

[0106] c. The third copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:50:1, anhydrous ethanol is added, and the solid content is adjusted to 10wt%; wherein the particle size of the copper powder is 1μm, and the particle size of the urea is 1.5μm;

[0107] 2) Preheating the copper foil substrate, and then coating the first copper foam layer slurry, the second copper foam layer slurry and the third copper foam layer slurry on the copper foil substrate in sequence. During the coating process, spraying a small amount of anhydrous ethanol on the surface of each layer of slurry to promote bonding and fusion between the layers;

[0108] 3) Place the coated copper foil in a vacuum sintering furnace, and under the protection of argon atmosphere, heat it to 700°C at a heating rate of 3°C / min and keep it at that temperature for 1 hour, so that the copper powder is sintered to form a gradient porous structure, and at the same time, urea decomposes to produce gas to form a gradient foam copper layer;

[0109] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried at a temperature of 70°C for 0.5 hours;

[0110] 5) mixing the negative electrode active material, graphene and lithium polyacrylate in deionized water at a mass ratio of 96:2:2, and stirring evenly to obtain a negative electrode active material coating slurry;

[0111] 6) coating the negative electrode active material coating slurry on one surface of the composite current collector and drying it to obtain the negative electrode sheet of the battery.

[0112] Preparation of positive electrode:

[0113] The positive electrode active material lithium nickel cobalt manganese oxide, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride are dispersed in the solvent NMP (N-methylpyrrolidone) in a mass ratio of 95:2:3 to form a uniform slurry, the slurry is evenly coated on the surface of the current collector aluminum foil, and then transferred to a vacuum drying oven for complete drying to obtain a positive electrode sheet.

[0114] Preparation of electrolyte:

[0115] Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1, and then fluoroethylene carbonate (FEC) is added at a volume percentage of 5%. Then, fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a concentration ratio of 1 mol / L to prepare an electrolyte.

[0116] Preparation of isolation film: A PET / PP composite film with a thickness of 15 microns was selected.

[0117] Preparation of lithium-ion batteries:

[0118] The negative electrode sheet, separator, and positive electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and the electrolyte is added, and a lithium-ion battery is assembled according to conventional processes.

[0119] Example 2

[0120] Different from Example 1, a multifunctional regulating coating 3 is further provided between the composite current collector 1 and the negative electrode active material coating 2 of the negative electrode of this embodiment. The multifunctional regulating coating 3 includes barium titanate, conductive carbon black and lithium polyacrylate. The mass ratio of barium titanate, conductive carbon black and lithium polyacrylate is 1:1:0.5; the thickness of the multifunctional regulating coating is 0.5 μm.

[0121] The preparation method of the negative electrode sheet is as follows:

[0122] 1) preparing a first copper foam layer slurry, a second copper foam layer slurry and a third copper foam layer slurry respectively;

[0123] a. The first copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:20:1, anhydrous ethanol is added, and the solid content is adjusted to 40wt%; wherein the particle size of the copper powder is 0.2μm, and the particle size of the urea is 0.4μm;

[0124] b. The second copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:30:1, anhydrous ethanol is added, and the solid content is adjusted to 25wt%; wherein the particle size of the copper powder is 0.5μm, and the particle size of the urea is 0.8μm;

[0125] c. The third copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:50:1, anhydrous ethanol is added, and the solid content is adjusted to 10wt%; wherein the particle size of the copper powder is 1μm, and the particle size of the urea is 1.5μm;

[0126] 2) Preheating the copper foil substrate, and then coating the first copper foam layer slurry, the second copper foam layer slurry and the third copper foam layer slurry on the copper foil substrate in sequence. During the coating process, spraying a small amount of anhydrous ethanol on the surface of each layer of slurry to promote bonding and fusion between the layers;

[0127] 3) Place the coated copper foil in a vacuum sintering furnace, and under the protection of argon atmosphere, heat it to 700°C at a heating rate of 3°C / min and keep it at that temperature for 1 hour, so that the copper powder is sintered to form a gradient porous structure, and at the same time, urea decomposes to produce gas to form a gradient foam copper layer;

[0128] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried at a temperature of 70°C for 0.5 hours;

[0129] 5) Mix barium titanate, conductive carbon black and lithium polyacrylate in a mass ratio of 1:1:0.5 in deionized water and stir evenly to obtain a multifunctional control coating slurry;

[0130] 6) coating the multifunctional regulating coating slurry on one surface of the composite current collector and drying it to obtain a composite current collector coated with the multifunctional regulating coating;

[0131] 7) applying an upward external electric field to the composite current collector coated with the multifunctional regulation coating to induce the barium titanate to form a directional polarization to construct a built-in electric field, wherein the direction of the built-in electric field is the direction from the surface of the composite current collector toward the outer surface of the multifunctional regulation coating;

[0132] 8) Mixing the negative electrode active material, graphene and lithium polyacrylate in deionized water at a mass ratio of 96:2:2, and stirring evenly to obtain a negative electrode active material coating slurry;

[0133] 9) coating the negative electrode active material coating slurry on the outer surface of the multifunctional regulating coating and drying it to obtain the negative electrode plate of the battery.

[0134] The rest is the same as in Example 1 and will not be described again here.

[0135] Example 3

[0136] Different from Example 1, in the composite current collector 1 of the negative electrode of this embodiment, the surface of the composite foam copper layer 12 is further provided with a carbon nano coating 13, and the thickness of the carbon nano coating 13 is 15 nm.

[0137] In addition, step 4) of the preparation method of the negative electrode plate also includes surface modification of the composite current collector 1 obtained after cooling, depositing a 15 nm thick carbon nanocoating 13, and hot rolling the surface modified composite current collector 1 on a precision rolling mill, with a rolling temperature of 120° C. and a rolling rate of 8%.

[0138] The rest is the same as in Example 1 and will not be described again here.

[0139] Example 4

[0140] Different from Example 1, in the composite current collector 1 of the negative electrode of this embodiment, the pore size d1 of the first copper foam 121, the pore size d2 of the second copper foam 122 and the pore size d3 of the third copper foam 123 satisfy the relationship: d1<d2<d3.

[0141] Specifically, in this embodiment, the pore size d1 of the first copper foam 121 is 3 μm, the pore size d2 of the second copper foam 122 is 8 μm, and the pore size d3 of the third copper foam 123 is 13 μm.

[0142] In addition, in step 1) of the preparation method of the negative electrode sheet, in the first foam copper layer slurry, the particle size of the copper powder is 0.1 μm, and the particle size of the urea is 0.3 μm; in the second foam copper layer slurry, the particle size of the copper powder is 0.5 μm, and the particle size of the urea is 0.8 μm; in the third foam copper layer slurry, the particle size of the copper powder is 1 μm, and the particle size of the urea is 1.3 μm.

[0143] The rest is the same as in Example 1 and will not be described again here.

[0144] Comparative Example 1

[0145] Different from Example 1, the negative electrode active material of this comparative example is silicon-carbon material without any modification or coating.

[0146] The rest is the same as in Example 1 and will not be described again here.

[0147] Comparative Example 2

[0148] Different from Example 1, the negative electrode active material of this comparative example is a silicon-carbon material and a single-walled carbon nanotube coating layer is provided on the outer surface of the silicon-carbon material.

[0149] The rest is the same as in Example 1 and will not be described again here.

[0150] Comparative Example 3

[0151] Different from Example 1, the negative electrode active material of this comparative example is a silicon-carbon material and a polypyrrole coating layer is provided on the outer surface of the silicon-carbon material.

[0152] The rest is the same as in Example 1 and will not be described again here.

[0153] Comparative Example 4

[0154] Different from Example 1, the negative electrode current collector of this comparative example adopts a copper foil current collector with a thickness of 10 μm.

[0155] The rest is the same as in Example 1 and will not be described again here.

[0156] Comparative Example 5

[0157] Different from Example 1, the negative electrode current collector of this comparative example adopts a single-layer foam copper current collector, and the foam copper current collector has a density of 0.5 g / cm³, a porosity of 90%, and a thickness of 10 μm.

[0158] The rest is the same as in Example 1 and will not be described again here.

[0159] The negative electrode sheets of the above embodiments and comparative examples were respectively subjected to ductility, stability and expansion rate tests, and the lithium-ion batteries with a capacity of 1Ah made from the negative electrode sheets were subjected to battery internal resistance and cycle performance tests. The test results are shown in Table 1.

[0160] Ductility test: Under the same pressure (20 tons), the negative electrode sheets prepared in the embodiment and the comparative example were rolled to observe whether there was brittle fracture or cracking on the surface of the electrode sheets. If any of the above phenomena occurred, it means that the ductility is poor.

[0161] Stability test: 10 negative electrode sheets prepared in the embodiments and comparative examples were respectively subjected to 90-degree folding and twisting experiments to observe the condition of the active materials at the folded or twisted parts. If any active materials fell off or broke, it indicated that the structural stability was poor.

[0162] Table 1

[0163] The test results of Table 1 above are analyzed as follows:

[0164] By comparing Example 1 with Comparative Examples 1 to 3, it can be seen that compared with the prior art of directly using silicon-carbon material as the negative electrode active material, or only coating single-walled carbon nanotubes on the outside of the silicon-carbon material as the negative electrode active material, or only coating a polypyrrole layer on the outside of the silicon-carbon material as the negative electrode active material, the present invention introduces a coating layer of polypyrrole and single-walled carbon nanotubes on the outer surface of the silicon-carbon material to form the negative electrode active material, which can effectively prevent the structural damage of silicon particles caused by volume change during charging and discharging, inhibit the expansion of the negative electrode, reduce the internal resistance of the battery, and improve the cycle life of the battery. This is because polypyrrole has high electrical conductivity, good environmental stability and strong charge storage capacity. Therefore, the polypyrrole layer, as a flexible coating layer, can buffer the volume change of silicon particles during charging and discharging, reduce stress accumulation, and improve the conductivity and structural stability of the electrode. Single-walled carbon nanotubes, with their high aspect ratio and flexibility, can continuously and effectively contact silicon materials during the cycle process to prevent the conductive network from breaking. The synergistic effect of the two can effectively inhibit the expansion and pulverization of silicon particles, maintain the integrity of the electrode structure, and improve the cycle life and stability of lithium batteries. Moreover, single-walled carbon nanotubes and graphene together form a line-surface conductive network, which significantly improves the conductivity of the electrode and reduces the battery interface impedance. The formed three-dimensional conductive network not only establishes a good conductive channel between the silicon-carbon negative electrode particles, but also can wrap, entangle or bind the negative electrode active material, further inhibiting the expansion of the negative electrode.

[0165] By comparing Example 1 with Comparative Examples 4 to 5, it can be seen that compared with the negative electrode prepared by the existing copper foil current collector or the single-layer foam copper current collector, the negative electrode of the present invention has better ductility, structural stability, lower expansion rate and battery internal resistance, because the negative electrode active material of the present invention has been infiltrated into the three-dimensional structure of the composite foam copper, and the gradient density composite foam copper itself has good flexibility, so it has a better retention effect on the active material infiltrated therein, thereby ensuring that the negative electrode prepared by the composite foam copper has better deformation resistance and structural stability during the processing process and the use of the battery, and can effectively prevent the negative electrode from brittle fracture or cracking, and effectively reduce the negative electrode expansion rate, so the lithium ion battery prepared by the negative electrode of the present invention has a higher cycle life.

[0166] By comparing Example 1 and Example 2, it can be seen that when a multifunctional control coating is provided between the composite current collector and the negative electrode active material coating, the negative electrode of the present invention has good ductility and structural stability, and can further reduce the negative electrode expansion rate and battery internal resistance. This is because the introduced barium titanate, as a ferroelectric material, can induce its internal dipoles to be oriented under the action of an external electric field, so that a uniform negative charge layer is formed on the surface of the composite current collector; this negative charge layer can promote Li +It is uniformly deposited on the surface of the negative electrode to inhibit the growth of lithium dendrites, thereby alleviating local stress concentration, reducing the degree of breakage of silicon particles, and extending the battery cycle life. On the other hand, barium titanate also has piezoelectric properties. During the cycle, the volume expansion of the composite material will cause the barium titanate lattice to deform, causing dynamic changes in the local built-in electric field. This dynamic electric field can guide lithium ions to migrate to areas with less stress, achieve uniform distribution of lithium ions, and avoid electrode pulverization failure caused by stress concentration. Therefore, the setting of a multifunctional control coating can further inhibit the expansion of silicon-based negative electrodes, improve lithium ion distribution, inhibit the growth of lithium dendrites, and improve battery cycle performance.

[0167] By comparing Example 1 and Example 3, it can be seen that when the surface of the composite foam copper layer of the negative electrode is further provided with a carbon nanocoating for surface modification, and the surface-modified composite current collector is further subjected to hot rolling treatment, the conductivity of the pole piece can be further improved, the battery resistance can be reduced, and it is beneficial to further improve the rate performance and cycle life of the battery.

[0168] By comparing Example 1 and Example 4, it can be seen that when the composite foam copper layer of the negative electrode adopts a pore size gradient distribution, a multi-level porous structure that is conducive to the embedding of active substances can be formed. The large pore size of the outer layer is conducive to the rapid transmission of electrolyte and lithium ions, and the small pore size of the inner layer can inhibit the volume expansion of the active substance and maintain the stability of the electrode structure. It can ensure that the negative electrode has a high specific surface area and high conductivity while taking into account better mechanical strength and structural stability, further improving the rate performance and cycle life of the battery.

[0169] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0170] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low expansion and low impedance lithium ion battery negative electrode, characterized in that: It includes a composite current collector and a negative electrode active material coating coated on at least one surface of the composite current collector; the negative electrode active material coating includes a negative electrode active material, graphene and lithium polyacrylate; the mass ratio of the negative electrode active material, the graphene and the lithium polyacrylate is (90~99):(0.5~5):(0.5~5), the negative electrode active material includes a silicon-carbon material and a coating material layer arranged on the outer surface of the silicon-carbon material, the coating material layer includes a polypyrrole layer and single-walled carbon nanotubes uniformly distributed in the polypyrrole layer.

2. The low expansion and low impedance lithium ion battery negative electrode according to claim 1, characterized in that: The silicon-carbon material is a mixture of silicon-based particles and graphite particles in a mass ratio of 1:(0.5-1); the particle size of the silicon-based particles is 10-50 nm.

3. The low expansion and low impedance lithium ion battery negative electrode according to claim 1, characterized in that: The particle size of the negative electrode active material particles is 0.2-2 μm.

4. The low expansion and low impedance lithium ion battery negative electrode according to claim 1, characterized in that: A multifunctional regulating coating is also arranged between the composite current collector and the negative electrode active material coating, and the multifunctional regulating coating includes barium titanate, conductive carbon black and lithium polyacrylate, and the mass ratio of the barium titanate, conductive carbon black and lithium polyacrylate is 1:1:(0.5~1).

5. The low expansion and low impedance lithium ion battery negative electrode according to claim 4, characterized in that: The thickness of the multifunctional regulating coating is 0.1-1 μm.

6. The low expansion and low impedance lithium ion battery negative electrode according to claim 1, characterized in that: The preparation method of the negative electrode active material is as follows: (1) mixing graphite particles and distilled water in a mass ratio of 1:(10-20), stirring for 1-3 hours, and uniformly mixing to form a first mixture; then adding silicon-based particles to the first mixture, stirring for 1-3 hours, and uniformly mixing the graphite particles and the silicon-based particles to form a second mixture; (2) mixing pyrrole monomer and single-walled carbon nanotube in a mass ratio of 1:(0.05-0.1), dissolving in a hydrogen chloride solution and stirring evenly to form a third mixture, wherein the mass ratio of pyrrole monomer to hydrogen chloride solution is 1:(1-5), then adding the second mixture to the third mixture, stirring for 0.5-2h, so that the second mixture and the third mixture are evenly mixed to form a fourth mixture; (3) dissolving ammonium persulfate in a hydrogen chloride solution to form a fifth mixture, wherein the mass ratio of ammonium persulfate to hydrogen chloride solution is 1:(1-5), adding the fourth mixture to the fifth mixture, stirring and reacting for 2-4 hours, filtering, washing and drying in sequence, and obtaining the negative electrode active material.

7. The low expansion and low impedance lithium ion battery negative electrode according to claim 1, characterized in that: The composite current collector includes a copper foil layer and a composite copper foam layer arranged on the copper foil layer, the composite copper foam layer includes a first copper foam, a second copper foam and a third copper foam arranged in sequence from the inside to the outside, the density ρ1 of the first copper foam, the density ρ2 of the second copper foam and the density ρ3 of the third copper foam satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first copper foam, the porosity φ2 of the second copper foam and the porosity φ3 of the third copper foam satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first copper foam, the thickness h2 of the second copper foam and the thickness h3 of the third copper foam satisfy the relationship: h1<h2<h3.

8. The low expansion and low impedance lithium ion battery negative electrode according to claim 7, characterized in that: The density ρ1 of the first copper foam is 0.5-0.9g / cm³, the density ρ2 of the second copper foam is 0.3-0.5g / cm³, and the density ρ3 of the third copper foam is 0.1-0.3g / cm³; the porosity φ1 of the first copper foam is 50-70%, the porosity φ2 of the second copper foam is 70-85%, and the porosity φ3 of the third copper foam is 85-95%; the thickness h1 of the first copper foam is 0.5-1μm, the thickness h2 of the second copper foam is 1-2μm, and the thickness h3 of the third copper foam is 2-4μm; the thickness h4 of the copper foil layer is 0.5-1μm; and the total thickness of the composite current collector is 4-8μm.

9. The low expansion and low impedance lithium ion battery negative electrode according to claim 7 or 8, characterized in that: The pore size d1 of the first copper foam, the pore size d2 of the second copper foam and the pore size d3 of the third copper foam satisfy the relationship: d1<d2<d3; the pore size d1 of the first copper foam is 1~5μm, the pore size d2 of the second copper foam is 5~10μm, and the pore size d3 of the third copper foam is 10~15μm.

10. A method for preparing a negative electrode for a lithium-ion battery with low expansion and low impedance according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) preparing a first copper foam layer slurry, a second copper foam layer slurry and a third copper foam layer slurry respectively; a. The first copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(15~25):1, anhydrous ethanol is added, and the solid content is adjusted to 30-50wt%; wherein the particle size of the copper powder is 0.1~0.4μm, and the particle size of the urea is 0.2~0.5μm; b. The second copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (25-35): 1, anhydrous ethanol is added, and the solid content is adjusted to 15-30wt%; wherein the particle size of the copper powder is 0.2-0.8μm, and the particle size of the urea is 0.4-1μm; c. The third copper foam layer slurry is made of copper powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, anhydrous ethanol is added, and the solid content is adjusted to 5-15wt%; wherein the particle size of the copper powder is 0.5-1.5μm, and the particle size of the urea is 0.8-1.8μm; 2) preheating the copper foil substrate, and then coating the first copper foam layer slurry, the second copper foam layer slurry and the third copper foam layer slurry on the copper foil substrate in sequence, and spraying a small amount of anhydrous ethanol on the surface of each layer of slurry during the coating process; 3) Place the coated copper foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the copper powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient foam copper layer; 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried; 5) Mixing the negative electrode active material, graphene and lithium polyacrylate in a mass ratio of (90-99):(0.5-5):(0.5-5) in deionized water and stirring evenly to obtain a negative electrode active material coating slurry; 6) coating the negative electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain the negative electrode of the lithium ion battery.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode and preparation method thereof

    CN111129427A

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN118016863A

  • Negative active material as well as preparation method and application thereof

    CN118572063A

  • Lithium battery silicon-based negative electrode material and preparation method thereof

    CN118748248A

  • Core-shell structure micron silicon-carbon composite material and preparation method therefor, electrode, and battery

    WO2023245986A1

Cited By

  • Negative electrode for lithium secondary battery and lithium secondary battery comprising same

    CN120127107A

  • Secondary battery and preparation method thereof, energy storage system and electric equipment

    CN120565613A

  • Low-rebound expansion material as well as preparation method and application thereof

    CN121172135A